1994
DOI: 10.1038/370527a0
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol-3-OH kinase direct target of Ras

Abstract: Ras (p21ras) interacts directly with the catalytic subunit of phosphatidylinositol-3-OH kinase in a GTP-dependent manner through the Ras effector site. In vivo, dominant negative Ras mutant N17 inhibits growth factor induced production of 3' phosphorylated phosphoinositides in PC12 cells, and transfection of Ras, but not Raf, into COS cells results in a large elevation in the level of these lipids. Therefore Ras can probably regulate phosphatidylinositol-3-OH kinase, providing a point of divergence in signalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

54
1,230
11
16

Year Published

1995
1995
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,844 publications
(1,319 citation statements)
references
References 35 publications
54
1,230
11
16
Order By: Relevance
“…This observation suggested that the signalling pathway mediated by periostin was acting through the PI3K/AKT pathway rather than through the RAF/ MEK/ERK pathway. However, our results do not exclude the possibility that K-Ras could contribute to periostin signalling by directly activating the PI3K complex (Rodriguez-Viciana et al, 1994).…”
Section: Discussioncontrasting
confidence: 90%
“…This observation suggested that the signalling pathway mediated by periostin was acting through the PI3K/AKT pathway rather than through the RAF/ MEK/ERK pathway. However, our results do not exclude the possibility that K-Ras could contribute to periostin signalling by directly activating the PI3K complex (Rodriguez-Viciana et al, 1994).…”
Section: Discussioncontrasting
confidence: 90%
“…In our experiments, MT binding to Shc and PI3K also seems to be essential for complete MAPK activation (data not shown). This is consistent with cooperation between the Ras and the PI3K pathways for full MAPK activation (Rodriguez-Viciana et al, 1994;Hu et al, 1995;Marra et al, 1995). However, high AP-1 activity is observed in the 250phe mutant (that does not bind Shc) even though the Erk1 activity displayed by this cell line is low.…”
Section: Discussionsupporting
confidence: 76%
“…This pathway mediates the signal into the nuclei, leading to activation of primary-response nuclear protooncogenes such as c-fos and c-myc by phosphorylation [5,6]. However, it is possible that ras p21 has effector proteins other than Raf-1, since ras p21 possesses multiple functions, pl20-GAP, p110 subunit of PI3-kinase, and MEKK are possible effector proteins of ras p21 in that these proteins interact with the GTP-bound form of ras p21 and that these proteins have an influence downstream of ras p21 in various signaling pathway [14][15][16][17]. However, several evidence has suggested that pl20-GAP and p110 subunit of PI3-kinase act as regulators of ras p21 [18,19].…”
Section: Introductionmentioning
confidence: 99%